Lichen diversity from Cazorla, Segura and Las Villas Biosphere Reserve (SE Spain) - Aragón V.J. Belinchón, R., G Rico (Nova Hedwigia, 2006)
The lichen flora from "Cazorla, Segura and Las Villas" mountains (SE Spain)" was investigated. A total number of 125 genera and 497 species were reported. Involucropyrenium waltheri, Placynthium asperellum, Strangospora deplanata, Verrucaria cinereoviridescens and V. polysticha are new cites for Spain and 267 taxa are new to the lichen flora of Jaén province. Other taxa (Agonimia allobata, A. octospora, Aspicilia lignicola, Bacidia absistens, B. subincompta, Bryoria capillaris, Calicium montanum, Caloplaca adriatica, Caloplaca assigena, Catapyrenium daedaleum, Lecanora coniferarum, L. densa, Lecidea hypopta, Leptogium burnetiae, Leptogium cretaceum, L. imbricatum, L. microphylloides, L. subaridum, Macentina dictyospora, Melaspilea urceolata, Placynthium hungaricum, Psora globifera, Psoroglaena stigonemoides, Protoparmelia oleagina, Psorotrichia frustulosa, Rinodina castanomela, R. dalmatica, R. furfuracea, Verrucaria canella, V. sorbinea and V. transiliensis) were specially considered due to their chorological and ecological implications within southern Europe regions. Valleys and ravines with dense forests stands (Quercus faginea, Q. rotundifolia) contain the highest lichen diversity (240 to 290 per km2) and the highest number of cyanophyllous species (45 to 65 per km2). Epiphytic lichen flora is different in humid and drier Pinus nigra forests. The major epiphytic diversity was located on bark of Q. faginea and Q. rotundifolia in well-preserved forests. Most terricolous species grew upper 1650 m altitude. Finally the majority of saxicolous lichens were found on vertical exposed rocks, in humid conditions, at altitudes from 1550 up to 1750 m. The lichen flora of the survey area is characterized by the high incidence of boreal-montane and temperate-oceanic element in epiphytic lichens and temperate-continental element in saxicolous and terricolous lichens.
Keywords: Epiphytic; Lichen diversity; Saxicolous; Terricolous (voyant)